The Transformation Wardrobe: Integrating Indonesian Batik and Modular Design for Sustainable Stage Wear - Puja Putri Kurnia Dewi; Adhi Kusumastuti (TEKNOBUGA: Jurnal Teknologi Busana dan Boga, 2026)
The global fashion industry is facing increasing environmental challenges due to rapid consumption patterns and the short lifespan of garments. This condition highlighted the urgent need for more sustainable design approaches. This study developed a transformable garment themed “Ratri Sagara” by adapting the visual elements of Batik Kencana Padjajaran, interpreted through the imagery of nocturnal ocean waves. The primary objective of the research was to create a garment design capable of presenting two distinct appearances through a simple transformation mechanism without excessive additional modules, thereby extending the product’s lifespan. The study employed a Research and Development (R&D) method based on the ADDIE model, encompassing the stages of analysis, design, development, implementation, and evaluation. The design process involved pattern-making and draping techniques, while feasibility evaluation was conducted by an expert panel using an assessment instrument consisting of six main indicators. The evaluation results showed an average score of 93%, placing the garment in the “Highly Feasible” category. The highest scores were achieved in the indicators of transformation performance and garment uniqueness, confirming the effectiveness of the transformation system and the innovative value offered. This research demonstrated that a transformable design approach can serve as an effective strategy for creating garments that are aesthetic, functional, and responsive to sustainability issues. The findings open opportunities for further development of transformation systems in contemporary fashion design, both for stage performance purposes and broader applications in everyday wear.